(untitled) (Shaheed Smriti Journal, 2024)
The Fifteenth Five-Year Plan of Nepal, launched under the slogan "Prosperous Nepal, Happy Nepali," set ambitious targets across various sectors. This article aims to evaluate the plan’s achievements by comparing its quantitative targets with actual outcomes, focusing on economic, educational, social, and demographic indicators. Using secondary data analysis, the study draws on data from the National Planning Commission (NPC) for fiscal years 2019/20 to 2022/23. The analysis highlights a mixed performance: while economic growth averaged 2.6%, poverty reduction improved by 20.3%, and education sector indicators showed positive outcomes, such as high literacy rates and enrollment in higher education. Several targets, especially in the demographic and social sectors, remained unmet. Notable shortfalls were observed in maternal and child mortality, internet access, and drinking water availability. The study concludes that while some progress was made, the gaps in achieving targets emphasize the need for more realistic planning, better resource allocation, and improved governance in future development strategies.